Ethnicity (Tribe) as a Socializing Agent in Nigerian Political Integration: The Case of the Ibos - Iwuji, Nnadozie Maurice (My University, 1978)
This Thesis seeks to demonstrate that ethnic cleavages on the part of the major Nigerian groups (the Hausa-Fulani, the lbo, and the Yoruba) coupled with the very nature of the British colonial heritage, made political integration impossible in Nigeria's first Republic. Nigeria was created artificially by the British to enhance Colonial objectives; there were not enough attempts by the Colonial administration to create a unified state. Moreover, 'Westernization' which has been usually associated with 'development' did not spread evenly across the country. The result, therefore, was competitive ethnic antagonism between the 'Westernized' Ibo and Yoruba on the one hand, and the 'non-Westernized' Hausa - Fulani on the other . This led to the ethnic political parties fighting bitterly to maximize their positions in national politics: elections were rigged, census figures distorted and undemocratic practices became rampant . The Army took over the government in a coup d'etat in January, 1966 and its aftermath was a civil war that finally destroyed the first Republic (1966 – 70).
This work is therefore concluding with the argument that, given the fragile nature of Nigeria's political existence, there should have been attempts on the Nigerian ethnic groups to accommodate one another through a form of elite cartel at the centre . An arrangement of this nature is usually known in the literature as "consociational democracy" (elite accommodation). Perhaps such a measure might have saved the state from crumbling the way it did.
Keywords: Political Science; Political Science